Export variety and economic growth in East European transition economies - Michael Funke; Ralf Ruhwedel (Bank of Finland, Institute for Economies in Transition (BOFIT), 2003)
Utilising panel data for 14 East European transition economies, we find support for the hypothesis that a greater degree of export variety relative to the U.S. helps to explain relative per capita GDP levels.The empirical work relies upon some direct measures of product variety calculated from 5-digit OECD trade data.Although the issue is far from settled, the emerging view is that the index of relative export variety across countries correlates significantly with relative per capita income levels.
URN:NBN:fi:bof-20140807292
Keywords: C33; F43; O31; O33; O52; 330; Product Variety; Transition Economies; Eastern Europe; Economic Growth; Panel Data